Distal transfers as a primary treatment in obstetric brachial plexus palsy: a series of 20 cases. (October 2016) - Ghanghurde, B. A.; Mehta, R.; Ladkat, K. M.; Raut, B. B.; Thatte, M. R.
The purpose of this study was to examine the results of spinal accessory nerve to suprascapular nerve (with or without axillary nerve neurotization) and an Oberlin transfer as primary treatment in children with Narakas type I obstetric brachial plexus injuries, when parents refused to consent to conventional nerve trunk-/root-level reconstruction. A total of 20 children with poor shoulder abduction and no biceps antigravity function but with good hand function were treated with spinal accessory nerve to suprascapular nerve and an Oberlin transfer at a mean age of 5.8 months (SD 3.27; range 3–12.) All the patients were evaluated at a mean of 2.8 years (SD 0.8; range 1.5 to 3.8) post-operatively. Three patients were lost to follow-up. Of the remainder, 11 had grade 4+ power of elbow flexion and six patients had grade 4 power at 1 year follow-up; all had 4+ power of elbow flexion at final follow-up. At final follow-up the Mallet score was a mean of 15; (SD 4.22, range 9 to 20). Primary distal nerve transfers can give good outcomes in patients with obstetric brachial plexus injuries and may be an alternative to surgery on the nerve trunks Level of evidence: IV